Oxidative and Nitrosative Stress in Age-Related Macular Degeneration: A Review of Their Role in Different Stages of Disease - Caterina Toma; Stefano De Cillà; Aurelio Palumbo; Divya Praveen Garhwal; Elena Grossini (MDPI AG, 2021)
Although the exact pathogenetic mechanisms leading to age-related macular degeneration (AMD) have not been clearly identified, oxidative damage in the retina and choroid due to an imbalance between local oxidants/anti-oxidant systems leading to chronic inflammation could represent the trigger event. Different in vitro and in vivo models have demonstrated the involvement of reactive oxygen species generated in a highly oxidative environment in the development of drusen and retinal pigment epithelium (RPE) changes in the initial pathologic processes of AMD; moreover, recent evidence has highlighted the possible association of oxidative stress and neovascular AMD. Nitric oxide (NO), which is known to play a key role in retinal physiological processes and in the regulation of choroidal blood flow, under pathologic conditions could lead to RPE/photoreceptor degeneration due to the generation of peroxynitrite, a potentially cytotoxic tyrosine-nitrating molecule. Furthermore, the altered expression of the different isoforms of NO synthases could be involved in choroidal microvascular changes leading to neovascularization. The purpose of this review was to investigate the different pathways activated by oxidative/nitrosative stress in the pathogenesis of AMD, focusing on the mechanisms leading to neovascularization and on the possible protective role of anti-vascular endothelial growth factor agents in this context.